2014
DOI: 10.5812/hepatmon.17976
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Telomerase Reverse Transcriptase mRNA in Peripheral Blood Mononuclear Cells of Patients With Liver Failure

Abstract: Background:Telomerase activity is closely associated with the expression of human telomerase reverse transcriptase (hTERT) mRNA; although it can be induced in hepatocytes during liver regeneration, its dynamic change in patients with liver failure has remained unclear.Objectives:We investigated the variation and significance of hTERT mRNA expression in peripheral blood mononuclear cells (PBMCs) of the patients with liver failure.Patients and Methods:In this clinical experimental study, 76 Chinese patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Increasing studies reported that human telomerase reverse transcriptase (hTERT) was a telomerase catalytic subunit and served as the major limiting agent for telomerase activity [3,4,38]. Telomerase activity was closely associated with the expression of hTERT mRNA [3,4,8,22], therefore hTERT mRNA expression was quantified by real-time fluorescent quantitative PCR to reflect telomerase activity (Fig.…”
Section: Mst-312 Inhibited the Inherent And Irradiation-induced Telommentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing studies reported that human telomerase reverse transcriptase (hTERT) was a telomerase catalytic subunit and served as the major limiting agent for telomerase activity [3,4,38]. Telomerase activity was closely associated with the expression of hTERT mRNA [3,4,8,22], therefore hTERT mRNA expression was quantified by real-time fluorescent quantitative PCR to reflect telomerase activity (Fig.…”
Section: Mst-312 Inhibited the Inherent And Irradiation-induced Telommentioning
confidence: 99%
“…Telomerase activity was closely associated with the expression of hTERT mRNA [3,4,8,22], therefore hTERT mRNA expression was quantified by real-time fluorescent quantitative PCR to reflect telomerase activity (Fig. 2).…”
Section: Mst-312 Inhibited the Inherent And Irradiation-induced Telommentioning
confidence: 99%